User Requirements Analysis for Developing a Web-Based Intelligent Attendance System in Vocational Schools - Encep Rafli Adi Putra Pratama; Ayu Puji Rahayu; Suyato Kusumaryono (Education and Sociedad Journal, 2025)
The student attendance process is an administrative activity that plays a crucial role in supporting attendance data management and fostering student discipline. However, manual attendance management still presents various challenges, such as relatively time-consuming recording, administrative errors, delays in information delivery, and the lack of integration of attendance data. This study aims to analyze the need for a Web-Based Intelligent Attendance System and to develop system specifications that meet user needs. The study employed a descriptive qualitative approach using observation, semi-structured interviews, and document analysis. The informants were teachers, students, and parents at SMK PK Nurussalam in Tasikmalaya Regency. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, through the stages of data condensation, data presentation, and conclusion drawing. The results indicate that the manual attendance process results in low administrative efficiency, limited data integration, weak information security, and suboptimal student attendance monitoring. Based on the analysis, 15 functional requirements were identified, including user authentication, digital attendance, time-stamping, automatic recapitulation, attendance dashboard, reports, parent notifications, and centralized data management. Furthermore, fifteen non-functional requirements were identified, including ease of use, data security, response speed, device compatibility, system reliability, and data backup mechanisms. The results of this needs analysis formed the basis for developing the specifications for a Web-Based Intelligent Attendance System, which is expected to support effective, efficient, and secure attendance management, while also orienting toward improving student attendance discipline.